Um circuito quântico para a correlação dos sinais do Arranjo Decimétrico Brasileiro (BDA) - Violin, Renato de Oliveira (Universidade Federal de São Carlos, 2010)
Quantum computation is a way to perform the computation based on the quantum physics. Since it is appeared in 1985, it promises a revolution in the data processing. Works that had already been done prove that quantum computation, regarding its features that comes from quantum physics, provides a better power computation than the classical computation. The goal of this work is to develop a quantum circuit that performs the correlation of the BDA (Brazilian Decimetric Array), a radiointerferometer that has been developed by INPE (National Institute of Space Research) to visualize cosmic objects through the detection of radiofrequencies radiated by these objects. It was studied some possible quantum circuits and made comparisons with the classical correlator circuit used in BDA. The comparison was made with respect to the number of operations needed to process the correlation in a integration period of 100 ms. The results show that the developed quantum correlator circuit uses less operations than the classical one, proving that the developed quantum circuit is more efficient than the corresponding classical circuit.
Keywords: Computação quântica; Somador quântico; Transformada de Fourier quântica; Radioastronomia; Correlação de sinais complexos; Quantum computation; Quantum adder; Quantum Fourier transform; Radioastronomy; Correlation; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO